Understanding antimicrobial resistance in Campylobacter isolates from poultry environments in Gujarat, India - Sadik Dantroliya; Monica Chavan; Ramesh Pandit; Chinmayi Joshi; Fiona Tomley; Damer Blake; Richard Stabler; Chaitanya Joshi; Madhvi Joshi (Applied Food Research)
Campylobacter, a pathogen responsible for human gastroenteritis on a global scale, is primarily spread through the consumption of contaminated chicken meat. Antimicrobial treatments are commonly required in response to campylobacteriosis, highlighting the risk posed by antimicrobial resistance (AMR) in Campylobacter to food safety and public health. Monitoring and understanding AMR trends is crucial for effective risk assessment and development of management strategies. The current investigation examines the physical and genetic traits of AMR in Campylobacter species found in the caeca of chickens. Samples were collected from chicken farms and live chicken retail outlets across eight major cities in Gujarat, India. Selective culture from 750 samples found 21 of 250 samples from farms (8.4 %) and 56 of 500 samples from outlets (11.2 %) contained Campylobacter spp., confirmed by multiplex PCR and Sanger sequencing. Campylobacter coli was most common, detected in 56 samples (7.5%), with Campylobacter jejuni detected in 21 samples (2.8%). As per phenotypic assay, all the isolates were resistant to antibiotics ampicillin/sulbactam, followed by azithromycin (94.44%). Genomes were sequenced from a subset of 16 C. coli and 2 C. jejuni isolates for identification of antimicrobial resistance genes (ARGs). Eleven isolates hosted fluoroquinolone and tetracycline resistance genes. Macrolide resistance genes, such as macB, were found in 94.4% of genomes. The results of the current research highlight a high occurrence of ARG carriage in C. jejuni and C. coli, suggesting that resistance to macrolides, quinolones, and tetracyclines is common. The genotype-phenotype concordance observed was 76.39% whereas, remaining discordance (23.61%) observed was due to the six AMR genes, of which two genes were found truncated length while the remaining genes had complete lengths but had mutations. In-depth examination of the linkage between genetic and phenotypic AMR traits can support development of future strategies and policies to address the growing problem of antibiotic resistance and protect public health.